2012
DOI: 10.1080/01973533.2012.674420
|View full text |Cite
|
Sign up to set email alerts
|

Evaluations of People Depicted With Facial Disfigurement Compared to Those With Mobility Impairment

Abstract: There are few extant studies of stereotyping of people with facial disfigurement. In the present study, two experiments (both within-participants) showed positive evaluations of people depicted as wheelchair users and, from the same participants, negative evaluations of people with facial disfigurements, compared to controls. The results of Experiment 2 suggested that implicit affective attitudes were more negative towards people with facial disfigurement than wheelchair users and were correlated with evaluati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 42 publications
(56 reference statements)
1
29
2
Order By: Relevance
“…The results of the present study are consistent with the observation in Stone and Wright (2012) that participants who perceived a stronger social norm for inclusion and equality for people with facial disfigurement also reported less prejudicial perceptions of their character traits and abilities. In the present study the perceived social norm was made more relevant to participants under conditions of relatively low anonymity and this resulted in lower reports of negative emotional experience.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…The results of the present study are consistent with the observation in Stone and Wright (2012) that participants who perceived a stronger social norm for inclusion and equality for people with facial disfigurement also reported less prejudicial perceptions of their character traits and abilities. In the present study the perceived social norm was made more relevant to participants under conditions of relatively low anonymity and this resulted in lower reports of negative emotional experience.…”
Section: Discussionsupporting
confidence: 82%
“…No research could be located that examined this question specifically for individuals with facial disfigurement. There is no reason to suppose that contact theory would not apply but it should be noted that levels of prejudice were relatively high for facial disfigurement compared to other factors including race and disability (Stone & Wright, 2012, 2013. The application of contact theory to individual with facial disfigurement would be an interesting line for future research.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The faces used in previous experiments (Stone & Wright, 2012;Stone & Potton, 2014) were used again in the present experiment. These comprised two male and two female faces, one of each gender with disfigurement to the eyes and the other with disfigurement to the mouth-cheek.…”
Section: Materials and Measuresmentioning
confidence: 99%
“…Disfigurement has been defined as a persistent and significant alteration to an individual's appearance (Krishna, 2009). According to the Changing Faces organisation one person in 111 in the UK has a disfigurement to the face (Changing Faces, Face Equality, 2014) and people with facial disfigurement experience stigmatisation due to their difference in appearance (e.g., Lawrence, Rosenberg, & Fauerbach, 2007;Stone & Wright, 2012). Individuals with facial disfigurement frequently report being stared at in public places (e.g., Jowett & Ryan, 1985) and other studies have reported heightened levels of negative emotional response to a disfigured face (Shanmugarajah, Gaind, Clarke, & Butler, 2012;Stone & Potton, 2014).…”
Section: Introductionmentioning
confidence: 99%